Hungary – the New Border of the European Union - Barta, Györgyi (Discussion Papers, 2012)
The present case study “Hungary - the new borders of the European Union” deals with the evolution of relationships between Hungary and its two neighbour¬ing countries, Romania and Serbia, after the fall of the communist regime. Hungary’s early EU accession created a novel situation. Once again, borders serve to separate Hungary from neighbouring non-EU countries, only temporarily in the case of Romania, but for a longer time in the case of Serbia. The purpose of the research is to highlight the old and new elements of the emerging forms of in¬tegration as well as the consequences of Hungary’s membership to the European Union over its neighbourhood policies for Romania and Serbia. The topic has been approached through a new research method. The research examines the development of relationships between Hungary and two neighbouring countries (Romania and Serbia-Montenegro) after the fall of the communist regime. Economic and social differences are exposed among the three countries both at the national level and in border regions. Special focus is given to the old and new elements of the emerging forms of integration, and the obvious consequences of EU membership of Hungary for its neighbour¬hood policies with Romania and Serbia-Montenegro.